Influence of mineral water of well No. 3 of Semyanivka village of Poltava district of Poltava region (Ukraine) on the structural and functional state of the kidneys with experimental nephritis - Gushcha, S.; Nasibullin, B.; Zukow, W.; Balashova, I.; Koieva, К.; Volyanska, V.; Arabaji, M. (Journal of Education, Health and Sport, 2019)
In an experiment on white rats with toxic nephritis, pathological changes in the structural and functional state of the kidneys were determined. An increase in the daily diuresis (p <0.001) was found, due to an increase in the glomerular filtration rate by (p <0.001) and a significant decrease in the percentage of fluid back-suction (p <0.001). The excretion of creatinine and urea increased by (p <0.01), and the excretion of chloride ions, on the contrary, decreased (p <0.01). Application on the background of the development of low-mineralized silicon chloride-hydrocarbonate sodium water leads to partial normalization of kidney function - the volume of diuresis is moderately restored by increasing the tubular reabsorption against the background of a significant increase in the glomerular filtration rate and a significant increase in the amount of silica. The manifestations of inflammation in the kidneys disappear, but the destructive changes of the nephrons remain. The partial restoration of the activity of redox enzymes has been established.